Safety and Efficacy of Nano‐Pulse Stimulation Treatment of Non‐Genital, Cutaneous Warts (Verrucae). Issue 10 (19th May 2021) - Nuccitelli, Richard; LaTowsky, Brenda M.; Lain, Edward; Munavalli, Girish; Loss, Lesley; Ross, E. Victor; Jauregui, Lauren; Knape, William A.
Abstract : Background and Objectives: This study describes the effects of nano‐pulse stimulation (NPS) technology on the common verruca with the objectives of demonstrating efficacy and safety. NPS technology applies nanosecond pulses of non‐thermal electrical energy to induce highly localized regulated cell death in the cellular structures of the targeted zone with negligible effects on surrounding non‐cellular structures. Previous clinical studies applying NPS to common, benign skin lesions have demonstrated safety and efficacy in clearing seborrheic keratoses and sebaceous hyperplasia. Study Design/Materials and Methods: Sixty‐two subjects were enrolled at a total of five sites. One hundred and ninety‐five study verrucae up to 10 mm wide were treated with NPS delivered by a console‐based handheld applicator (CellFX® System; Pulse Biosciences) and follow‐ups occurred every 30 days with the option to retreat at 30, 60, and 90 days. There were 62 untreated controls and 46% of the treated verrucae were recalcitrant. Results: Overall, 75.3% (70/93) of the common verrucae, 72.7% (8/11) of the flat verrucae, and 43.8% (14/32) of the plantar verrucae treated with NPS were completely clear by 60 days following the last treatment and did not recur within the 120‐day observation period. The majority (54%) of verrucae cleared with a single NPS procedure. The most common treatment site reactions were erythema (50.5%) and eschar formation (23.4%) on Day 30 and on Day 120 mild erythema was present in 14% of the cases and hyperpigmentation in 18.5%. No serious adverse events were reported. A particle counter was used during 11 NPS procedures on verrucae and no significant plume generation was detected during these procedures. Conclusions: NPS is a safe and effective procedure for removing non‐genital, cutaneous verrucae. Lasers Surg. Med. © 2021 The Authors. Lasers in Surgery and Medicine published by Wiley Periodicals LLC.